KEWAJIBAN TENAGA KESEHATAN DALAM MEMBERIKAN INFORMED CONSENT: KAJIAN LITERATUR ETIKA DAN HUKUM - Gunawan Widjaja; Hotmaria Hertawaty Sijabat; Handojo Dhanudibroto (CV. ADIBA AISHA AMIRA, 2025)
This study aims to examine the obligations of health workers in providing informed consent from an ethical and legal perspective through a literature review. Informed consent is an essential communication process between health workers and patients prior to medical procedures, which affirms the patient's right to obtain complete information and to give conscious and voluntary consent. Legally, this obligation is regulated in various regulations in Indonesia, such as Law No. 29 of 2004, Law No. 36 of 2009, and Law No. 17 of 2023, and reinforced by medical professional ethical standards. The results of the study indicate that optimal implementation of informed consent can protect patients' rights while providing legal protection for healthcare providers; however, challenges remain in its implementation, such as time constraints, the use of medical terminology that is difficult to understand, and insufficient education for both patients and healthcare providers. Therefore, efforts to enhance understanding, training, and continuous supervision are needed to ensure that ethical and legal principles in the provision of informed consent are truly realised in healthcare practice in Indonesia.